Application of Two-Level Full Factorial Design for the Extraction of Fucoxanthin and Antioxidant Activities from Sargassum siliquosum and Sargassum polycystum - Lim, Michelle Wen San; Tan, Kar Mem; Chew, Lye Yee; Kong, Kin Weng; Yan, See Wan (Taylor & Francis, 2018)
Two-level full factorial design was employed to identify the extraction parameters that can improve the derivation of fucoxanthin content (FC), total carotenoid content (TCC), and antioxidant from two brown seaweeds, Sargassum siliquosum (SS) and Sargassum polycystum (SP). These parameters included temperature (A: 4–45°C), time (B: 30–1,440 min), and solvent-to-solid ratio (C: 10–50 ml/g). Antioxidant activities were determined as trolox equivalent antioxidant capacity (TEAC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity, and ferric-reducing antioxidant power (FRAP). Results showed that all three factors were significant (p < 0.05) in providing higher FC in both species. These factors were also significant in obtaining higher TCC in SS; whereas in SP, TCC was only affected by solvent-to-solid ratio. Only temperature was found to contribute significantly to a higher TEAC in both species. However, none of the factors improved DPPH for SS, except temperature and time for SP. For SS, only time was significant in obtaining higher FRAP; whereas temperature and time were significant for SP. Hence, results indicate that a simple modification in the extraction temperature, time, and solvent-to-solid ratio will be able to improve the derivation of fucoxanthin, carotenoids, and antioxidant activities.